Corrosão em meio salino de uma liga Al-Mg-Sc submetida à deformação plástica severa por torção sob alta pressão e ao recozimento em temperaturas de 523 a 773 k - Michelle Dias Alves Lage (2021)
Modification’s influence in crystalline structure of a material caused by severe plastic deformation (SPD), such as high-pressure torsion (HPT) in the corrosion behavior of metallic materials is not yet well understood. This work evaluated the influence of HPT in the corrosion behavior of an Al-3%Mg-0.2%Sc as-cast alloy through electrochemical tests of electrochemical impedance spectroscopy (EIS), cyclic polarization, Mott-Schottky analyses, X-ray photoelectron spectroscopy (XPS) and chronoamperometry in a 3.5% (wt.%) NaCl solution. It was observed that the passive current decreased after processing by HPT, indicating the formation of a more protective oxide layer in the processed alloy surface. The Mott-Schottky analysis confirmed the high protection efficiency of the oxide layer in the processed material by the low defects concentration in the oxide formed. The film formed in the as-cast alloy was characteristic of type p and type n semiconductor, while the processed by HPT alloy just presented a film type n semiconductor behavior. The EIS analysis showed improvement in the corrosion resistance in saline environment after the HPT processing. The materials were characterized by scanning electron microscopy (SEM) after the corrosion tests. In order to evaluate the influence of grain size and distribution in the alloy corrosion behavior, the processed by HPT material was subjected to annealing in different temperatures and the annealed alloy corrosion resistance was evaluated through EIS and potentiodynamic polarization tests in 3.5% (wt.%) NaCl solution. Analysis of Nyquist and Bode diagrams suggested better corrosion resistance in materials the presented a more homogeneous grain distribution and the polarization data indicated higher corrosion current density to the samples which present a more heterogeneous grain structure. The materials were characterized by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and SEM and the images suggested more corrosion sensibility in the samples that have a more heterogeneous grain distribution after annealing process.